Investigating the interplay between initial hard processes and final-state effects measuring prompt and non-prompt J/ψ - Coquet Maurice (EPJ Web of Conferences)
Charmonium production in high-energy collisions can be split into a prompt and a non-prompt component. Both components can be distinguished experimentally by studying displaced topology, and represent valuable tools to investigate the properties of the strongly interacting medium produced in ultrarelativistic heavy-ion collisions. In particular, the study of non-prompt charmonium production can give access to the beauty-hadron production cross section and can be used to investigate the in-medium energy loss of beauty quarks. In these proceedings, the recent measurement of prompt and non-prompt J/ψ carried out by the ALICE Collaboration in Pb–Pb collisions at midrapidity (|y| < 0.8) at √sNN = 5.02 TeV, will be presented. Moreover, thanks to the installation of the new muon forward tracker (MFT), the prompt/non-prompt charmonium separation will be possible in LHC Run 3 also at forward rapidity (2.5 < y < 4).